The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s11096-017-0536-1
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of pre-warming, hot compress, and pH adjustment in oxaliplatin-induced venous pain

Abstract: Background Venous pain induced by peripheral intravenous administration of oxaliplatin remains clinically unresolved. Objective The aim of this study was to determine the efficacy of comprehensive intervention care for venous pain in colorectal cancer patients receiving oxaliplatin. Setting A Japanese tertiary hospital. Method We treated all outpatients after April 2012 with comprehensive intervention care including pre-warming of the oxaliplatin solution, use of a hot compress, and pH adjustment by combinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Co-infusion of dexamethasone 7 , prewarming peripheral blood vessels 16 , premedication with oxycodone, and altering the dose rate have all been investigated as countermeasures against oxaliplatin-induced vascular pain 6 . The effects of many of these countermeasures on vascular pain were assessed by VAS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-infusion of dexamethasone 7 , prewarming peripheral blood vessels 16 , premedication with oxycodone, and altering the dose rate have all been investigated as countermeasures against oxaliplatin-induced vascular pain 6 . The effects of many of these countermeasures on vascular pain were assessed by VAS.…”
Section: Discussionmentioning
confidence: 99%
“…Heating the blood vessels is thought to reduce vascular pain 16 . Furthermore, blood flow is known to increase with increasing vessel diameter 17 , and Hagen Poiseuille’s equation showed that blood flow increased in proportion to the fourth power of the vessel diameter 18 .…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it was reported that warming the blood vessels might reduce oxaliplatin-induced venous pain. 19 Therefore, it was proposed that the application of a hot pack would result in the dilation of blood vessels, which may be useful to reduce symptoms of vascular pain after intravenous gemcitabine administration. Indeed, as shown in Figure 1B, our results indicated that the incidence of vascular pain in patients with hot pack use was significantly lower than that in patients without hot pack use, with dosages >930 mg/m 2 .…”
Section: Discussionmentioning
confidence: 99%
“…These approaches include accessing the large vein in the crease of the forearm for peripheral venipuncture, reducing the speed of administration, increasing the volume of dilution, 14,15 addition of dexamethasone into the solution for pH adjustment, 16,17 administration through a Y-site of the main infusion route of a hydration bag, 18 and warming the vein with a hot pack. 19 However, the efficacy of these methods for preventing vascular pain caused by administration of anticancer drugs, including gemcitabine, has not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…We believe that the graphene @VER-M or nano Fe 3 O 4 @VER-M system would be useful for mild PTT in the future. Or more succinctly, other kinds of heat treatments for cancer therapy such as hot compress 80 and hyperthermic perfusion 81 could be enhanced by forming hot compress@VER-M or hyperthermic perfusion@VER-M system.…”
Section: Discussionmentioning
confidence: 99%